HUBUNGAN PENGUATAN GURU TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN IPS TERPADU DI SMPN 25 KABUPATEN SOLOK SELATAN - Helmadona, Helmadona; Zafri, Zafri; Husnita, Liza (Pendidikan Sejarah, 2014)
Low motivation of student to learn especially in studying the science of social subjectin Junior High School 25 Kabupaten Solok Selatan. History Education Program. STKIP PGRI West Sumatera. Padang 2014. The background of this research is low motivation of student to learn especially in studying the science of social subject. Based on that problem, this research focuses on reinforcement of teachers to motivate students especially in the science of social subject in Junior High School 25 Solok Selatan. The primary purpose of this research is to find relationship reinforcement of teachers to studentâs motivation in the science of social course.Types of research that used in this research are descriptive correlation. The population of this study is all of students in Junior High School 25, Solok Selatan 2013/2014, and the sample of this research are 46 students which taking with Proportional stratified random sampling technique with Slovin formula. The result of this research describes reinforcement of teachers to students motivation in Junior high school 25 Solok Selatan in medium (39, 13%), meanwhile students motivation in Junior High School lower (46, 65%). The result of hypothesis evidence there are relationship between reinforcement of teachers to students motivation in Junior high School 25 Solok Selatan, the relationship of reinforcement of teachers to students motivation is lower with r count = 0,317 with r table 0,294, but the direction of relationship is positive because the value of r is positive. This study describes the results that reinforcement of teachers influence motivation in general, however discussed separately but was not correlated. This finding suggests that reinforcement essentially no impact in isolation, but overall influence student motivation. It means if the teacher give motivation, so that the student motivation will be arise.Â